The Influence of Madrasah Principals' Exemplary Behavior on Teachers’ Character in Pandeglang - Een Masdariah; Umdatul Hasanah (International Journal of Nusantara Islam, 2026)
This study critically examines the influence of principals’ exemplary leadership on the formation of teacher character in Islamic junior secondary schools (madrasah thanawiyah) under the Ministry of Religious Affairs in Pandeglang Regency. Exemplary leadership is conceptualized as the embodiment of moral integrity, ethical conduct, and professional consistency, whereas teacher character is measured through indicators of integrity, professional ethics, discipline, responsibility, and spiritual commitment. Using a quantitative survey approach involving 34 principals and teachers, the study employed validated instruments that were tested through Exploratory Factor Analysis and Cronbach’s alpha reliability procedures. The findings reveal that principals’ exemplary leadership is rated highly, predominantly driven by moral and spiritual dimensions, while teacher character is rated very highly. A positive perception gap was identified, with teachers evaluating their principals more positively than principals evaluated themselves, suggesting strong moral legitimacy and symbolic authority attributed to school leaders. Challenges remain in the area of principals’ technical professionalism, which requires systematic enhancement. The study recommends integrative leadership development programs that combine ethical modeling with managerial competence. This research advances theoretical understanding of social learning processes in Islamic education, demonstrates the empirical role of moral leadership in shaping teacher character, and offers practical insights for policy formulation in strengthening madrasah leadership quality.